FSKKP thesis formatting application - Mohd Raheemmi, Mohd Yasin (2010)
FSKKP Thesis Formatting Application (FTFA) will be developed with the object to help student to produce a thesis document that follows the Faculty of Computer System & Software Engineering (FCSSE) thesis standard. The current application being use by student are the normal word processing applications that also provide the features to produce thesis but it just following the general standard without any specific thesis standard. Other than that, FTFA is expected to be able to reduce the mistakes made by the student in producing thesis document due to their carelessness., Therefore, this project is carried outto build an application that will specifically provide thesis document processor that follow accurately to the FCSSE thesis standard. Rapid Application Development method will be use as the framework for the development of the FTFA. The development FTFA will go through four phases in RAD which are requirement planning phase, user design phase, construction phase and cutover phase. FTFA will be developing using PHP as it programming language on a Windows platform workstation. Overall, the development of FTFA is hoped to help students who take final year project to perfecting their thesis document.